Bond behavior and failure mechanism of fiber-reinforced polymer bar–engineered cementitious composite interface. (15th September 2021) - Zhao, Debo; Zhou, Yingwu; Xing, Feng; Sui, Lili; Ye, Zenghui; Fu, Huankai
Highlights: Bond behaviors of FRP bars in ECC were investigated experimentally and numerically. Splitting failure is prevented due to the post-crack resistance of ECC. Effects of geometric structure of rebar surface on bond behavior were investigated. A simplified bond failure model was established based on the pullout failure mode. Abstract: The bond performance of engineered cementitious composites (ECCs) and fiber-reinforced polymer (FRP) bars was investigated via pullout tests. The experimental results indicated that increasing the ECC strength led to a proportional increase in the bond strength, and rebars with higher ribs exhibited higher bond strengths (by a maximum of 55%) than counterparts with lower ribs. A finite-element model of an ECC thick-walled cylinder was developed to examine the interfacial bond failure mechanism and was validated by experimental data. Experimental and simulation results indicated that owing to the excellent post-crack resistance of the ECC material, splitting failure at the rebar–ECC interface was prevented, and the shear resistance of ECC corbels between the rebar ribs significantly affected the bond failure. A simplified bond-strength model was then developed according to the pullout failure mode, and a new equation for the bond strength that accounts for the surface configuration of the rebar was derived.